The Effect of Electrical Muscle Stimulation on Muscle Mass and Balance in Older Adults with Dementia - Yuichi Nishikawa; Tetsuya Takahashi; Shuhei Kawade; Noriaki Maeda; Hirofumi Maruyama; Allison Hyngstrom (Brain Sciences, 2021)
Background: Electrical muscle stimulation (EMS) is effective for increasing physical function. However, there is no evidence regarding the effects of EMS on muscle mass and physical function in older adults with dementia. The aim of the present study was to quantify the effects of EMS on muscle mass and balance in older adults with dementia. Methods: A total of 32 participants were randomly assigned to an intervention group (n = 16, age = 89.4 ± 4.8 years) and a control group (n = 16, age = 88.1 ± 5.2 years). Participants in the intervention group underwent a general rehabilitation program (20 min for three days/week) and an EMS intervention (23 min for three days/week) for 23 weeks. Participants in the control group underwent general rehabilitation only. The efficacy of EMS was evaluated by lower limb muscle mass, the Berg Balance Scale (BBS), and the functional independence measure (FIM). Results: Muscle mass was significantly increased in the intervention group after 12 weeks (p = 0.008), but average muscle mass in the control group did not change (p = 0.18). Participants in the control group showed a significant decrease in BBS after 12 weeks (p = 0.007), unlike those in the intervention group. Furthermore, there was a strong correlation between the mini-mental state examination (MMSE) results and the change in muscle mass, the BBS, and the FIM in the control group (p < 0.05). Conclusions: These findings suggest that EMS is a useful intervention for increasing muscle mass and maintaining balance function in older adults with dementia.